Integration of artificial intelligence and robotics in rehabilitation therapy: enhancing motor recovery after injury or stroke - Bajaj, Gaurav; Davu, Gayathri; Viswanathan, B. (International Journal of Research in Medical Sciences, 2025)
Background: Artificial intelligence (AI) and robots are revolutionizing healthcare by delivering intelligent, adaptable, and patient-centric solutions. These technologies restore motor function, improve therapeutic precision, and adapt patient treatment regimens, making them vital for rehabilitation therapy. Recent advances in neuroscience, motor control, robotics, and AI-based algorithms have opened new doors in brain and motor rehabilitation. Invasive and non-invasive human-machine interfaces can reduce the long-term effects of strokes and spinal cord injuries. This research examines how AI and robotics can improve motor recovery after injury or stroke in rehabilitation therapy. Methods: This study utilizes the quantitative research methodology. Data were gathered from different clinical trials and studies that specifically examined AI-assisted robotic rehabilitation therapy. Important indicators consist of the enhancement in motor function, rates of patient adherence, and the overall efficacy of therapy. A total of 19 participants were selected for this investigation. The standard of care group had ten participants and the robotic therapy group nine. Results: The study showed that robotic therapy improved all evaluations more than the control group, proving that AI and robotic technology work in rehabilitation therapy. Conclusions: The findings demonstrate that AI-integrated robotic therapy outperforms normal care in rehabilitation. Subsequent research endeavours may delve deeper into the enduring advantages and enhance the treatment regimens to optimize patient recuperation.